2012
DOI: 10.2478/v10222-011-0037-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Smoking on Indicatory Congeners Residues Levels in Fish Slices

Abstract: The aim of this study was do determine changes in concentrations of indicatory PCB congeners (IUPAC numbers: 28, 52, 101, 118, 153, 138, 180) during industrial hot smoking of mackerel (Scomber scombrus L.) and herring (Clupea harengus L.) slices and cold smoking of mackerel slices. PCB content in raw mackerel slices averaged from 1.32±0.29 ng/g wet w. for PCB 52 to 4.66±0.72 ng/g wet w. for PCB 153. In herring slices, PCB content ranged from 1.36±0.25 ng/g wet w. for PCB 28 to 16.50±1.94 ng/g wet w. for PCB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The deep fried fish products analysed contained high levels of organochlorine pesticides such as HCB, Dieldrin, p, pꞌ-DDE and Lindane as compared to other products like trims, salted-sundried and smoked products probably due to environmental contamination that occurs along the food chain as seen in Table 1. Smoking of fish tends to increase the levels of persistent organochlorine compounds due to a decrease in co-distillation with steam and the penetration of the compounds with smoke to the fish meat (Witczak and Tomza-Marciniak, 2010;Witczak, 2012). Our findings support this as most of the smoked samples had significant quantities of different persistent organochlorine pesticides.…”
Section: Hchsupporting
confidence: 74%
“…The deep fried fish products analysed contained high levels of organochlorine pesticides such as HCB, Dieldrin, p, pꞌ-DDE and Lindane as compared to other products like trims, salted-sundried and smoked products probably due to environmental contamination that occurs along the food chain as seen in Table 1. Smoking of fish tends to increase the levels of persistent organochlorine compounds due to a decrease in co-distillation with steam and the penetration of the compounds with smoke to the fish meat (Witczak and Tomza-Marciniak, 2010;Witczak, 2012). Our findings support this as most of the smoked samples had significant quantities of different persistent organochlorine pesticides.…”
Section: Hchsupporting
confidence: 74%
“…It is also suspected that some processors use transformer oils for fish frying and consumption of smoked fish products is common in the area. Both transformer oil and smoke are good sources of PCBs in the environment and environmental compartments (Wenaty et al, 2019a;Witczak, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There is therefore a need to investigate the impacts of smoking on fish products from Lake Victoria. Another study which was done on fried fish products revealed that deep frying reduces the levels of PCBs in fish due to the fact that; (i) deep frying process creates unique cooking conditions that accelerates drying of the fillets (ii) evaporation of water and PCBs from the fillets as a result of high temperature of the cooking oil and by transfer of PCBs to the cooking oil which itself could be acting as an extraction solvent (Witczak and Ciereszko, 2012), though the same compounds are likely to be reintroduced into fish muscles as the cooking oil is reused in subsequent fish processing. Such studies have not been undertaken in Africa and in Lake Victoria in particular thus it is necessary that a study be designed to reveal the prevalence of PCBs and how safe the fish products are.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are mainly found in lipid-rich food of animal origin, such as meat, fish and dairy products, which constitute an important part of our daily diet. It has been suggested that food of animal origin is responsible for more than 90% of the average human intake of polychlorinated biphenyls PCBs and OCPs [2]. One common feature of OCPs is that they bio-accumulate in the food chain and in the human body, and, as a consequence, represent a potential risk for the human health [3,4].…”
Section: Introductionmentioning
confidence: 99%